The Mayo Clinic Author Catalog: A Living Repository of Medical Knowledge - Key, Jack D. (1973)
Since 1907 records have been kept of publications by staff members of the Mayo Clinic, and this information has been invaluable. The Author Catalog has proved itself such a useful tool for the Mayo Clinic that other libraries, large and small, may wish to consider adopting such a service. The Mayo medical complex is a large institution with more than 500 staff and faculty members engaged in the publication of clinical, educational, and research findings. The great amount of cross-disciplinary cooperation and interdepartmental research makes essential an up-to-date record of what is going on. The Mayo Clinic Library developed a comprehensive computerized method for identifying research and for identifying and indexing publications of Mayo staff members. At the end of 1971 more than 25,000 citations had been stored on computer tape.